Streets of Laredo - McMurtry, Larry (New York : Simon & Schuster, 1993)
A handsome young psychopath begins a spree of train robberies and murder in West Texas border country, and the victimized railroad hires the legendary Ranger Captain Woodrow Call to stop him.
Sequel to: Lonesome dove.
Keywords: Outlaws -- Fiction; Western stories